Rosiglitazone, a PPAR-gamma ligand, protects against burn-induced oxidative injury of remote organs - ŞENER, GÖKSEL (ELSEVIER SCI LTD, 2007)
Severe burn induces the activation of an inflammatory cascade that contributes to the development of subsequent immunosuppression, increased susceptibility to sepsis, as well as generation of reactive oxygen radicals and lipid peroxidation, leading to multiple organ failure. In the present study, we investigated whether rosightazone, a peroxisome proliferator-activated receptor-gamma (PPAR-gamma) ligand is protective against burn-induced remote organ injury. Under brief ether anaesthesia, shaved dorsum of the rats were exposed to 90 degrees C (burn group) or 25 degrees C (control group) water bath for 10 s. Rosiglitazone (4 mg/kg) or saline was administered intraperitoneally immediately after and at the 12th hour of the burn. Rats were decapitated 24 h after injury and the tissue samples from lung, liver, and kidney were taken for the determination of malondialdehyde (MDA) and glutathione (GSH) levels, myeloperoxidase (MPO) activity and collagen contents. Serum aspartate aminotransferase (AST), alanine aminotransferase (ALT) levels, and creatinine, blood urea concentrations (BUN) were determined to assess liver and kidney function, respectively. Serum levels of tumor necrosis factor-alpha (TNF-alpha), interleukin-1 beta (IL-1 beta) and lactate dehydrogenase (LDH) were also assayed. Severe skin scald injury (30% of total body surface area) caused a significant decrease in GSH level, and significant increases in MDA level, MPO activity and collagen content of tissues. Similarly, serum ALT, AST and BUN levels, as well as LDH, IL-1 beta and TNF-alpha were elevated in the burn group as compared to the control group. Rosiglitazone treatment reversed all these biochemical indices. According to the findings of the present study, rosiglitazone possesses a anti-inflammatory effect that prevents burn-induced damage in remote organs and protects against organ damage. (c) 2006 Elsevier Ltd and ISBI. All rights reserved.
Keywords: burn injury; rosiglitazone; neutrophil; oxidative damage; cytokines; glutathione; ACTIVATED-RECEPTOR-GAMMA; THERMAL-INJURY; LIPID-PEROXIDATION; FREE-RADICALS; BACTERIAL TRANSLOCATION; ACUTE-INFLAMMATION; RATS; ISCHEMIA; PLASMA; MYELOPEROXIDASE